2017
DOI: 10.7554/elife.26280
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive action of peripheral mu-opioid receptors by G-beta-gamma protein-mediated inhibition of TRPM3 channels

Abstract: Opioids, agonists of µ-opioid receptors (µORs), are the strongest pain killers clinically available. Their action includes a strong central component, which also causes important adverse effects. However, µORs are also found on the peripheral endings of nociceptors and their activation there produces meaningful analgesia. The cellular mechanisms downstream of peripheral µORs are not well understood. Here, we show in neurons of murine dorsal root ganglia that pro-nociceptive TRPM3 channels, present in the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
95
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 93 publications
2
95
1
Order By: Relevance
“…It is not clear why herkinorin behaves differently from PZM21 and TRV130 in reversing the effects of DAMGO, and we have not further investigated this difference. Also, our data with herkinorin on PregS‐induced Ca 2+ signals in DRG neurons are at odds with those of Dembla et al, who showed that herkinorin evoked an inhibitory effect similar to that induced by DAMGO in the same assay (Dembla et al, ). It was also shown that in DRG neurons, 10‐μM herkinorin induced an inhibitory effect on N‐type voltage‐gated Ca 2+ channels similar to that induced by 1‐μM DAMGO (Rowan et al, ).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…It is not clear why herkinorin behaves differently from PZM21 and TRV130 in reversing the effects of DAMGO, and we have not further investigated this difference. Also, our data with herkinorin on PregS‐induced Ca 2+ signals in DRG neurons are at odds with those of Dembla et al, who showed that herkinorin evoked an inhibitory effect similar to that induced by DAMGO in the same assay (Dembla et al, ). It was also shown that in DRG neurons, 10‐μM herkinorin induced an inhibitory effect on N‐type voltage‐gated Ca 2+ channels similar to that induced by 1‐μM DAMGO (Rowan et al, ).…”
Section: Discussioncontrasting
confidence: 97%
“…G βγ subunits have multiple targets including G‐protein‐coupled inwardly rectifying potassium channels (K ir 3; Logothetis, Kurachi, Galper, Neer, & Clapham, ) and voltage‐gated Ca 2+ channels (N‐type and P/Q‐type; Currie, ). A recently described target of G i signalling is the TRPM3 ion channel, which is robustly inhibited by G βγ subunits (Badheka et al, ; Dembla et al, ; Quallo et al, ). Non‐ion channel targets of G βγ include phosphoinositide 3‐kinase‐γ (PI3Kγ) and MAPKs (Clapham & Neer, ; Khan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While TRPM3 -/mice show defects in noxious heat sensation, the channel shows increased activity well below the noxious range, when temperature is increased from 15 o C to 26 o C, with further increases in activity at 37 o C (Vriens et al, 2011). TRPM3 is also inhibited by activation of Gi-coupled receptors such as μ-opioid receptors and GABAB receptors in DRG neurons, and agonists of those receptors reduced nocifensive reactions to local injection of TRPM3 agonists (Badheka et al, 2017;Dembla et al, 2017;Quallo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the activation of Gi-coupled receptors influence the activity of Piezo2 channels has not been studied yet. Activation of Gi-coupled receptors leads to inhibition of adenylate cyclase, activation of G-protein coupled inwardly rectifying K + (GIRK) channels and inhibition of voltage-gated Ca 2+ channels (VGCC) and of transient receptor potential melastatin 3 (TRPM3) channels in DRG neurons through direct binding of Gβγ (Badheka et al, 2017;Dembla et al, 2017;Quallo et al, 2017;Reuveny et al, 1994;Robertson and Taylor, 1986). In addition, Gβγ is also known to induce the activation of phosphoinositide 3-kinase gamma (PI3Kγ) and mitogen-activated protein kinase (MAPK) (Clapham and Neer, 1997;Khan et al, 2013;Lopez-Ilasaca et al, 1997;Touhara et al, 1995).…”
Section: Introductionmentioning
confidence: 99%